REGENERAÇÃO DE ESPÉCIES LENHOSAS EM PLANTIO DE SCHINUS MOLLE L. (AROEIRA - PERIQUITA) E TREMA MICRANTHA L. BLUME (GRANDIÚVA) - Trindade, Débora F. V. d.; Coelho, Geraldo C. (Salão do Conhecimento, 2013)
Resumo